Effect of androgen excess and glucocorticoid exposure on metabolic risk profiles in patients with congenital adrenal hyperplasia due to 21-hydroxylase deficiency. Issue 197 (March 2020) - Paizoni, Luisa; Auer, Matthias K.; Schmidt, Heinrich; Hübner, Angela; Bidlingmaier, Martin; Reisch, Nicole
Highlights: Metabolic health in patients with congenital adrenal hyperplasia (CAH) is good. CAH men are prone to increased relative body fat mass, insulin resistance is more common in CAH women. Hydrocortisone use is superior in terms of body composition in comparison to synthetic glucocorticoids. Arterial hypertension is rare, but 54 % of patients have an impaired systolic drop at night. Impaired dipping is independently mediated by higher sodium levels. Abstract: Data on cardiovascular morbidity in adults with congenital adrenal hyperplasia (CAH) is sparse. We therefore aimed to determine the role of androgen control and glucocorticoid therapy on metabolic health. For that purpose, we included 90 patients (N = 39 men, N = 51 women) with classic CAH due to 21-hydroxylase deficiency (N = 61 salt wasting, N = 29 simple virilizing) and an equal number of controls matched for age, sex, BMI and smoking-habits. We could show that there was no difference in intima-media-thickness between patients and controls and only one patient fulfilled all criteria of the metabolic syndrome. CAH men presented with an increased relative body fat mass in comparison to controls (25.6 % vs. 22.1 %; p = 0.011) while this was not true for CAH women. Body fat was lower in those taking hydrocortisone instead of synthetic glucocorticoids (B = -3.27; p = 0.048). While arterial hypertension was rare, 54 % of patients had an impaired systolic drop at night or were classified as non-dippers (17 %). Impaired dipping was not associated with evening glucocorticoid and fludrocortisone intake but mediated by sodium levels. Insulin resistance was more common in CAH women (B = 1.689; p = 0.036) and in those with poor androgen control (B = 0.823; p = 0.046). In summary, we could show that good cardiovascular health outcome in adult CAH patients can be achieved. Hydrocortisone is superior in terms of body composition. It is yet unclear how non-dipping will translate into cardiovascular morbidity in the long-term.